Sustaining Plurilingual Meaning-Making in Digital Music Ecologies: A Critical Multimodal Discourse Analysis of Intercultural Communication Practices - Saiyidinal Firdaus (Journal of Linguistics and Social Studies, 2026)
This study investigates how plurilingual meaning-making is sustained and reshaped within digital music ecologies through multimodal discourse practices. Grounded in a language ecology perspective and Critical Multimodal Discourse Analysis (CMDA), the research examines multilingual interactions across YouTube and Instagram, focusing on captions, comments, visual symbolism, and platform affordances. The findings reveal that plurilingual competence emerges as an adaptive ecological process in which linguistic, visual, and affective resources operate collaboratively to facilitate intercultural mediation. Rather than relying on fixed language boundaries, participants engage in translanguaging, symbolic alignment, and multimodal negotiation to construct shared interpretations across diverse cultural backgrounds. The analysis further demonstrates that algorithmic infrastructures and participatory practices play a significant role in shaping intercultural dialogue by amplifying certain communicative strategies while enabling localized linguistic expressions to coexist within global digital networks. The study contributes theoretically by integrating plurilingual competence and multimodality into a unified analytical framework, highlighting the importance of digital cultural spaces as informal sites of multilingual learning and mediation. Pedagogically and policy-wise, the findings suggest the need to reconceptualize multilingual education and language planning to account for multimodal literacies and technologically mediated communication practices.